Movie Recommender System Based on K-Means Dynamic Collaborative Filtering - Murugan, S Ananda; Pramoth, V; Raja, P M Prasannth; Ragupathi, S (Annals of the Romanian society for cell biology, 2021)
KEY WORDS: recommender system;content-based;collaborative; hybrid 1.INTRODUCTION A recommendation system is a class of information filtering system that predicts a customer's "rank" or "preference" for a particular object. [...]mining online feedback for movie opinions has become a more urgent practise that has drawn a lot of attention from researchers. [...]novel Relational Adaptive bootstrapping (RAP) algorithm is proposed owing to lengthen the seeds inrequiredarea using labelled origin data and correlationamong subject as well as sentiment terms. [...]using a graph-based algorithm, opinion targets are extracted, with opinion relevance of candidate calculated from mined union combined along candidate significance for producing a common metric.